Real-Time Dynamic Optimal Power Flow in Electric Vehicles Considering the Lifetime of the Components in the E-Powertrain - Erfan Mohagheghi; Joan Gubianes Gasso; Pu Li (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
Different types of energy sources (e.g., batteries, supercapacitors, fuel cells) can be utilized in electric vehicles to store and provide energy in the e-powertrain through power electronic devices [1-6]. The lifetime of the components in the e-powertrain depends on their load profile [7,8]. For instance, the lifetime of a battery highly depends on the depth of discharge and the number of charge/discharge cycles [9-13].